Immanence, idéalité et inclusion: Husserl lecteur de Berkeley - Farges, Julien (Bollettino Filosofico, 2024)
This article examines the relationship between Husserlian phenomenology and Berkeley’s empiricism and attempts to reconstruct the reasons why, despite the untenable nature of Berkeley’s immaterialism, Husserl recognizes nevertheless its crucial importance for the idea of phenomenology. First, the paper shows that Berkeley’s intermediate position between Locke and Hume enables Husserl to see in his empiricism a philosophy of pure immanence capable of raising the question of the foundation of transcendence without falling into skepticism. It then shows that Berkeley’s phenomenological critique, on both sides of the transcendental turn, relies on the idea of intentional content to demonstrate that ideality can be included in this immanence without being reduced to one of its parts. Keywords: Berkeley, Husserl, Immanence, Ideality, Inclusion